Is it possible a new educational alliance? (Nóema, 2016)
The paper suggests a minute inspection of Ilya Prigogine’s theses concerning a new alliance between scientific inquiry and humanistic culture. The point at issue is the overcoming of Cartesian dualism in school and in society, in view of an innovating historical consideration of nature and man.
Keywords: prigogine; scientific inquiry; humanistic culture